Inhabiting the museum - Anna Calise (AN-ICON, 2023)
The present contribution wants to investigate how the use of technology is redefining the performative role of visitor bodies within museum environments. It will address the topic of the physical body of museum goers as an experiential tool and discuss to what extent its active, at times performative, use across museum settings has been and is considered as an important element of the cultural experience. This research offers a storeographical account which begins from visitor engagement in the early 17th to 19th century museums, continues with an account of the ‘disappearance’ of the visitor body in modern museums (Candlin, 2004), and proceeds analysing the revival of a more systemic and bodily understanding of these spaces (Howes, 2014), with technologies playing a very important role in incentivizing and characterizing this shift. The case for the positive interplay between museums and technological artistic experience towards a performative engagement of the visitor’s physical presence will be made through the case study of the Nxt Museum, in Amsterdam. The specific project that will be here analyzed is the Shifting Proximities exhibition, which explores human experience and interaction in the face of social and technological change. Through this last institutional account the research will complete its itinerary through performative action across museum experiences in time and space, arguing for the relevance that technological media can play in transforming visitors’ relationship with art through their bodies.